The Relationship of Sugar-Sweetened Beverages (SSB) Consumption with Nutritional Status in Adolescents at SMKN 32 Jakarta - Khoirul Anwar; Novtia Ristiana Khalda (Journal of Applied Science for Pharmaceuticals and Health, 2024)
Nutritional problems such as obesity are a health problem that still occurs in all parts of the world. The incidence of nutritional status is influenced by many things, including excessive energy intake from food and drinks, such as Sugar-sweetened beverages (SSB). This study aims to identify the relationship between consumption of Sugar-sweetened beverages (SSB) and nutritional status among adolescents at SMKN 32 Jakarta. This research used a cross sectional research design with 80 research subjects who were students aged 16-18 years who attended SMKN 32 Jakarta who were selected using consecutive sampling. Data on consumption of Sugar-sweetened beverages (SSB)was obtained from the BEVQ-15 (Beverage Questionnaire) questionnaire during the last month. Female subjects experienced more nutritional status at 77.1% compared to male respondents who were overnourished at 22.9%. Most of the research subjects were teenage girls and boys who often consumed soft drinks seen from the frequency distribution of consumption of sugar sweetened beverages and were teenagers who had more nutritional status. The results showed that there was a relationship between the frequency of sugar-sweetened drink consumption and the nutritional status of respondents who consumed soft drinks (p=0.010). The conclusion in this study is that there is a relationship between consumption of sugary sweet drinks and overweight status in adolescents at SMKN 32 Jakarta. Keywords: Adolescents, Consumption of Sugar Sweetened Beverages, Nutritional Status